Optical Emission of the Nuclear-Induced Plasmas of Gas Mixtures. (27th April 2014) - Khasenov, Mendykhan U.
Abstract : The characteristic properties of the inverted-population-forming processes in lasers with ionizing pumping are considered. Results obtained from research of active laser media concerning the p-s transitions of atoms of neon, mercury, and cadmium are presented. The feasibility of ion-ion recombination in lasers with nuclear pumping is discussed. The excitation kinetics of the first negative system of CO, heteronuclear ionic molecules of inert gases, and halogenides of inert gases under ionizing radiation are considered.